Intravenous thrombolysis + endovascular thrombectomy versus thrombolysis alone in large vessel occlusion mild stroke: a propensity score matched analysis. (24th February 2023) - Schwarz, Ghil; Bonato, Sara; Lanfranconi, Silvia; Matusevicius, Marius; Ghione, Isabella; Valcamonica, Gloria; Tsivgoulis, Georgios; Paiva Nunes, Ana; Mancuso, Michelangelo; Zini, Andrea; Candelaresi, Paolo; Rand, Viiu‐Marika; et al.
Abstract: Background and purpose: The best reperfusion treatment for patients with mild acute ischaemic stroke harbouring proximal anterior circulation large vessel occlusion (LVO) is unknown. The aim was to compare the safety and efficacy of intravenous thrombolysis (IVT) plus endovascular thrombectomy (EVT) versus IVT alone in LVO patients with mild symptoms. Methods: From the Safe Implementation of Treatment in Stroke–International Stroke Thrombolysis and Thrombectomy Register (SITS‐ISTR), were included: (i) consecutive acute ischaemic stroke patients, (ii) treated within 4.5 h from symptoms onset, (iii) baseline National Institutes of Health Stroke Scale (NIHSS) score ≤5 and (iv) intracranial internal carotid artery [ICA], M1 or T occlusion [defined as occlusion of ICA terminal bifurcation]. After propensity score matching, 3‐month functional outcomes (modified Rankin Scale [mRS] 0–1 and 0–2) and safety outcomes (symptomatic intracerebral haemorrhage and death) were compared (via univariable and multivariable logistic [and ordinal] regression analyses) in patients treated with IVT + EVT versus IVT alone. Results: In all, 1037 patients were included. After propensity score matching ( n = 312 per group), IVT + EVT was independently associated with poor functional outcomes (adjusted odds ratio [aOR] 0.46 for mRS 0–1, 95% confidence interval [CI] 0.30–0.72, p = 0.001; aOR 0.52 for mRS 0–2, 95% CI 0.32–0.84, p = 0.007; aOR 1.61 for 1‐point shift in mRS score, 95% CI 1.12–2.32, p = 0.011), with no significant differences in safety outcomes compared to IVT alone, despite numerically higher rates of symptomatic intracerebral haemorrhage (3.3% vs. 1.1%; p = 0.082), a higher rate of any haemorrhagic transformation (17.6% vs. 7.3%; p < 0.001) and subarachnoid haemorrhage (7.9% vs. 1.5%; p = 0.002) in the IVT + EVT group. Discussion: In anterior circulation LVO patients presenting with NIHSS score ≤5, IVT + EVT (vs. IVT alone) was associated with poorer 3‐month functional outcome. Randomized controlled trials are needed to elucidate the best treatments in mild LVO patients.